2015
DOI: 10.1177/0091217415592369
|View full text |Cite
|
Sign up to set email alerts
|

Designing and implementing a resiliency program for family medicine residents

Abstract: Family medicine residents are at risk for burnout due to extended work hours, lack of control over their work schedule, and challenging work situations and environments. Building resiliency can prevent burnout and may improve a resident's quality of life and health behavior. This report describes a program designed to build resiliency, the ability to bounce back from stress, in family medicine residents in a medium sized U.S. residency training program. Interactive sessions emphasized building self-awareness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 19 publications
1
59
0
4
Order By: Relevance
“…This deliberate focus on resilience in the face of adversity can have a powerful effect on the optimism of both patient and provider. The approach fits well within an existing literature supporting that resilience can be enhanced deliberately through self-care acts like adequate rest and exercise [21] and through social support and use of cognitive coping skills [1].…”
Section: Individual Treatmentsupporting
confidence: 63%
“…This deliberate focus on resilience in the face of adversity can have a powerful effect on the optimism of both patient and provider. The approach fits well within an existing literature supporting that resilience can be enhanced deliberately through self-care acts like adequate rest and exercise [21] and through social support and use of cognitive coping skills [1].…”
Section: Individual Treatmentsupporting
confidence: 63%
“…46 These have included the use of exercise, 47 Balint/supervision/discussion groups 48 and mindfulness/meditation training. 49 A recent review of programmes to reduce burnout in physicians 50 (either individual or organisational interventions) found that stress management programmes (as well as mindfulness-based and small group discussions) were successful in reducing burnout scores, although few studies assessed the long-term effects of the programmes.…”
Section: Previous Interventionsmentioning
confidence: 99%
“…Similarly, concerns about social stigma when practising mindfulness is a reality that will require leadership and role modelling by attendings and residents to offset. The suggestion to briefly practise as a group prior to rounds has been previously studied with inpatient nurses21 and resident physicians 31. The approach was reported to be relatively easy to implement and well received by participants; however, the influence on provider and patient outcomes requires further study.…”
Section: Discussionmentioning
confidence: 99%